The effect of local nucleotides on synonymous codon usage in the honeybee (Apis mellifera L.) genome - Cutler R.W. (2014)
Using all currently predicted coding regions in the honeybee genome, a novel form of synonymous codon bias is presented that affects the usage of particular codons dependent on the surrounding nucleotides in the coding region. Nucleotides at the third codon site are correlated, dependent on their weak (adenine [A] or thyamine [T]) versus strong (guanine [G] or cytosine [C]) status, to nucleotides on the first codon site which are dependent on their purine (A/G) versus pyrimidine (C/T) status. In particular, for adjacent third and first site nucleotides, weak-pyrimidine and strong-purine nucleotide combinations occur much more frequently than the underabundant weak-purine and strong-pyrimidine nucleotide combinations. Since a similar effect is also found in the noncoding regions, but is present for all adjacent nucleotides, this coding effect is most likely due to a genome-wide context-dependent mutation error correcting mechanism in combination with selective constraints on adjacent first and second nucleotide pairs within codons. The position-dependent relationship of synonymous codon usage is evidence for a novel form of codon position bias which utilizes the redundancy in the genetic code to minimize the effect of nucleotide mutations within coding regions. © 2007 Springer Science+Business Media, LLC.